Servios urbanos e perspectivas concretas de criaao de trabalho em Recife: em busca da integraf ao dospobres e do desenvolvimento socioespacial - Moura de Castilho, Cláudio Jorge (Universidad del Rosario, 2010)
This article focuses on the relationshi p between service activities and work market in Recife/Brazil, searching for social and spatial development. Service activities have increased a lot during the last twelvc ycars; moreover,  these  activities  h ave  bee n u nderstood by society as an opportunity to find a work and/or an occupation, searching for their social and spatial mobility. On the other hand, the local elites promotc thc idea of spatial and social development based on spatial actions in the city, in order to create the illusion of development; but the social and spatial development never happens due to local developing conditions. That's why we have to think in another urban policy for working in the city; conditions sine qua non it cannot promote the development.